Inspeç\~ao do trabalho e evoluç\~ao do emprego formal no Brasil - Carlos Henrique L. Corseuil; Rita Almeida; Pedro Carneiro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– Labor inspection procedures in Brazil went through important changes in several dimensions from late 90s to mid 2000, improving the procedures efficiency. In the subsequent period formal employmentexpanded significantly. The aim of this paper is to identify whether the first fact influenced the latter. In order to do so, we analyzed municipality level data from 1996 to 2006 on labor inspection intensity and job flows. According to our results, more intense labor inspections tends to increase job creation when we use an indicator of labor inspection frequency as a proxy for intensity. The relation becomes negative when we use an indicator of efficiency as a proxy for intensity. Regarding job destruction it seems to be affected only by the frequency indicator.
Keywords: J21; 330; Arbeitsschutz; Brasilien